Experiences of belonging and discrimination among LGBTIQ+ individuals in male single-sex schooling environments - Du Toit, Jordan (My University, 2020)
This research explores the experiences of queer individuals who attended single-sex male schools, and the possible effects single-sex schooling have on supporting or subverting homophobia and transphobia in South Africa. With the advent of post-apartheid schooling in South Africa, legislation has become very progressive, but questions remain about whether policy enactment on the ground has moved too slowly, and whether, in many cases, could be skirted by institutions reluctant to embrace change. This research aims to unpack the sometimes traumatic and sometimes resilience-building experiences queer participants had in male single-sex schools. This is done within a framework of intersectionality analysing data through narrative analysis. Single-sex schools are shown to impact adolescent identity formation when it comes to gender identity and/or sexual orientation. School and peer cultural perceptions were found to be deeply connected to peer-group belonging, friendships and incidences of violence related to bullying and discrimination for these individuals. All participants were found to have been witness to violence –whether directly or through the visible homophobia that targeted more openly queer learners at the schools. The process of this research highlighted the isolation many queer learners feel within the male schooling system and necessitates future engagement with the way these schools run. The overtly hyper-masculine and racist cultures being enshrined in these schools are found to often marginalise queer learners, especially queer learners of colour. This research concluded that single-sex male schools cannot hope to become an active part of the South African transformation agenda while such toxic cultures are still being perpetuated in building future generations of South Africans. It is hoped future research could use this work to expand interest into the voices of queer South Africans and their experiences of the schooling system to facilitate constructive discussion around change and inclusivity moving forward
A research report submitted to the University of Witwatersrand, Faculty of Humanities, in partial fulfilment of the requirements for the degree Masters of Arts in Clinical Psychology (Coursework and Research Report) University of the Witwatersrand, 2020